Marriage, Celibacy, and Heresy in Ancient Christianity: The Jovinianist Controversy. By David G. Hunter - Hartney, Aideen (The journal of theological studies, 2008)
A significant number of studies of early Christian society in recent years have focused on the phenomenon of asceticism—the manner in which some Christians expressed their devotion by renouncing all worldly distractions, including food, sleep, and sexual contact. The extreme nature of this behaviour and the extent to which it was admired by contemporary audiences have understandably attracted much scholarly attention and we could be forgiven for assuming that the discourse of early Christianity was shaped predominantly by such dramatic figures who cut themselves off from conventional society and often practised impressive feats of penance.